The Effect of Helicobacter pylori Eradication on the Levels of Essential Trace Elements. (25th June 2014) - Wu, Meng-Chieh; Huang, Chun-Yi; Kuo, Fu-Chen; Hsu, Wen-Hung; Wang, Sophie S. W.; Shih, Hsiang-Yao; Liu, Chung-Jung; Chen, Yen-Hsu; Wu, Deng-Chyang; Huang, Yeou-Lih; Lu, Chien-Yu
Abstract : Objective . This study was designed to compare the effect of Helicobacter pylori ( H. pylori ) infection treatment on serum zinc, copper, and selenium levels. Patients and Methods . We measured the serum zinc, copper, and selenium levels in H. pylori -positive and H. pylori -negative patients. We also evaluated the serum levels of these trace elements after H. pylori eradication. These serum copper, zinc, and selenium levels were determined by inductively coupled plasma mass spectrometry. Results . Sixty-three H. pylori -positive patients and thirty H. pylori -negative patients were studied. Serum copper, zinc, and selenium levels had no significant difference between H. pylori -positive and H. pylori -negative groups. There were 49 patients with successful H. pylori eradication. The serum selenium levels were lower after successful H. pylori eradication, but not significantly (P = 0.06 ). There were 14 patients with failed H. pylori eradication. In this failed group, the serum selenium level after H. pylori eradication therapy was significantly lower than that before H. pylori eradication therapy (P < 0.05 ). The serum zinc and copper levels had no significant difference between before and after H. pylori eradication therapies. Conclusion . H pylori eradication regimen appears to influence the serum selenium concentration (IRB number: KMUH-IRB-20120327).